Walt Whitman Rostow'un Kalkınma Aşamaları Yaklaşımına Göre Gaziantep Ekonomisinin Incelenmesi - Metin Yıldırım; Ibrahim Örnek (Turkish Economic Association, 2012)
– Development Stages of W.W Rostow have five basic stages: Traditional Society, Society at the Preparatory Period for Take Off (Transitional Society), Society at the stage of Take off, Society at the stage of Drive to Maturity and Society at Age of High Mass Consumption. Introducing the similarities and dissimilarities of the country's economic history, Rostow tried to put the development level of countries in his theory which holds all development levels from poor agricultural community to mass consumption economy. As one of the most important industrial and commercial centers of Turkey, Gaziantep has a great economic power with its wide variety of rich outputs produced in industry and trade in both its region and country. With its hectic pace of growth, Gaziantep has become a model for developing cities. Gaziantep had experienced the stage of Traditional Society prior to 1930's, years between 1930 and 1979 could be defined as Transitional Stage then it has passed to Take Off Stage at 1980's and still experiences that stage. It is possible for Gaziantep to pass to the Maturity Stage soon, if the dynamism on its economy that carry the desire of becoming a brand city could be carried on and the investments towards education, culture and innovation could be increased.
Keywords: 330; Rostow; development; growth; take off; economy of Gaziantep